2005
DOI: 10.1111/j.1748-5967.2005.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Rearing of Chrysopa pallens (Rambur) (Neuroptera: Chrysopidae) on Artificial Diet

Abstract: An artificial rearing method was designed for the generalist predator, Chrysopa pallens (Rambur). The rearing media were formulated based on, Orius strigicollis diets for feeding larvae, and two diets for adults were prepared with insect source and non‐insect as their main components. Development of the predators was successfully obtained with the diets for both larval and adult stages. The impact of these diets was recorded for growth during the larval stage and oviposition rates by the females. Total develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
1
15
3
Order By: Relevance
“…Our results are very close to Ulhaq et al, (2006) work which reported total larval and pupal periods on artificial diet (hen's Syed et al, (2008) evaluated larval and pupal mortality of C. carnea on egg of S. cerealella (1 st =0, 2 nd =5, 3 rd =5 and pupal=10%), Sattar et al, (2007) reported when predator fed on two artificial diets the results were as followed LD= 14.25,65 (%) and PD=17.33, 74.9 (%) as similar as present studies. Lee and Lee (2005) reported immature mortality of C. pallens on artificial diet (1 st =0.6, 2 nd =0, 3 rd =0.4 and pupal= 11%) differs from our finding on semi artificial diet which is related to different composition of artificial diets and predator's species. Artificial diet was used in Lee et al, (2005) as similar as present semi artificial diet but it is contained of some common Antibiotics (penicillin and streptomycin) which may affect in predator's development.…”
Section: The Developmental Timescontrasting
confidence: 56%
See 2 more Smart Citations
“…Our results are very close to Ulhaq et al, (2006) work which reported total larval and pupal periods on artificial diet (hen's Syed et al, (2008) evaluated larval and pupal mortality of C. carnea on egg of S. cerealella (1 st =0, 2 nd =5, 3 rd =5 and pupal=10%), Sattar et al, (2007) reported when predator fed on two artificial diets the results were as followed LD= 14.25,65 (%) and PD=17.33, 74.9 (%) as similar as present studies. Lee and Lee (2005) reported immature mortality of C. pallens on artificial diet (1 st =0.6, 2 nd =0, 3 rd =0.4 and pupal= 11%) differs from our finding on semi artificial diet which is related to different composition of artificial diets and predator's species. Artificial diet was used in Lee et al, (2005) as similar as present semi artificial diet but it is contained of some common Antibiotics (penicillin and streptomycin) which may affect in predator's development.…”
Section: The Developmental Timescontrasting
confidence: 56%
“…Lee and Lee (2005) reported immature mortality of C. pallens on artificial diet (1 st =0.6, 2 nd =0, 3 rd =0.4 and pupal= 11%) differs from our finding on semi artificial diet which is related to different composition of artificial diets and predator's species. Artificial diet was used in Lee et al, (2005) as similar as present semi artificial diet but it is contained of some common Antibiotics (penicillin and streptomycin) which may affect in predator's development.…”
Section: The Developmental Timescontrasting
confidence: 56%
See 1 more Smart Citation
“…Unfortunately, no comparisons were made between individuals fed artificial diet versus a control, such as natural (live) prey. Lee and Lee (2005) reported that Chrysopa pallens (Rambur) larvae were reared on an artificial diet containing insect components (powdered A. pernyi pupae), beef liver, beef powder, and chicken egg yolk. C. pallens larvae required 27 days to complete development and mortality was 11%.…”
Section: Benefits and Limitations Of Artificial Diets Containing Insementioning
confidence: 99%
“…The larvae of C. sinica forage actively and are voracious predators of various species of prey (Xu et al, 1999;Duelli, 2001) and frequently used in augmentative and inundative biological control of agricultural pests (Zhou et al, 1991;Senior & McEwen, 2001). In order to optimize the conditions used by biocontrol companies to rear C. sinica and achieve a more cost effective method of rearing various other species of prey and artificial diets have been used (Lee & Lee 2005;Uddin et al, 2005;Kazemi & Mehrnejad, 2011). However, mass rearing techniques are still relatively inefficient.…”
Section: Introductionmentioning
confidence: 99%